Mouse milk somatic cell count in coagulase negative Staphylococcus species induced mastitis (Journal of Laboratory Animal Science, 2024)
Bovine mastitis is an economically important disease of bovines and caused by multi etiological factors in which bacteria  is the major cause. In the present study, milk somatic cell count (SCC) in mouse mastitis induced by Staphylococcus  epidermidis, S. chromogenes, S. haemolyticus and S. aureus isolated from apparently normal bovine milk was studied. The  2 x 104 cfu organisms in 50 µl per teat were inoculated through intramammary route in 4th and 5th pairs of abdominal  mammary gland in mice. The squeeze method, a technique was developed and standardized for milk collection from  mice at 6, 12, 24, 48, 72 and 96 hr after intramammary inoculation (IMI). The milk somatic cell count was estimated  using NucleoCounter SCC-100®. The mouse milk ranging from 50 to 200 µl per mice was collected successfully. The  milk somatic cell count showed significant increase in S. aureus inoculated mice at 6, 12, 24 hr and increase was two to  four folds when compared to PBS control. The three coagulase negative staphylococcus species showed increased SCC  levels at 24, 48, 72 and 96 hr after IMI. Thus, Coagulase negative staphylococci (C) species can increase the mice milk  somatic cell count moderately but two to four fold increase was observed in S. aureus which indicated the subclinical  nature of CNS infections in animals. Mouse is a suitable model to study coagulase negative staphylococcus species  induced bovine subclinical mastitis.
Keywords: epidermidis; chromogenes; haemolyticus